The Australian Yodda: A massive, mysterious, and pan-continental flaked stone oddity. Issue 1 (2nd January 2021) - Maloney, Tim; Akerman, Kim; Street, Mervyn
Abstract: The Yodda is a large flaked stone artefact found across Australia in rare, isolated contexts, subject to almost no archaeological study. Yoddas are rare artefacts, which to date have only been collected as isolated surface finds. In an attempt to move towards an understanding of these enigmatic objects, we present an analysis of Yoddas ( n = 27) known to us from Australian collections, and review early collector observations from Australia. While their original cultural significance remains obscure, we suggest esoteric trade values are likely uses, underlying the production of these large, non-optimal, yet pan-continental, stone artefacts.